Políticas públicas departamentales aplicables para controlar la contaminación y reducción del caudal del arroyo Isabel López - Atlántico (2021)
The present work has the general objective of investigating the problem of contamination and reduction of the flow of the Arroyo Isabel López as well as its instability, and the public policies, especially departmental ones, applicable to control this situation. Isabel López is a district assigned to the jurisdiction of the municipality of Sabanalarga, department of Atlántico. This work is necessary due to the problem being studied, and no other research was found on the ecological and public health problem that Arroyo de Isabel López represents in the state in which it is located. The research is of a socio-legal nature, qualitative in nature. Its specific objectives are to identify the factors that have caused pollution and reduction of the flow of the Isabel López Creek, review the environmental regulations that guide the public policies of the department of Atlántico in terms of protection of channels and quality of water bodies and propose measures improvement to control pollution and maintenance of the flow of the mentioned stream. The presentation of this work is divided into chapters. Chapter I contains the titles Research problem, Objectives and Justification. Chapter two contains the Theoretical Framework, Geographical Framework, Historical Framework and Legal Framework. Chapter III comprises the methodological framework. Then the Conclusions, Recommendations and the sources consulted are offered in References.